KARAKTERISTIK FISIK-KIMIA BULU BABI Diadema setosum DARI BEBERAPA PERAIRAN PULAU AMBON - Tupan, Johanna; Silaban, Bernita br (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2017)
The existence of Diadema setosum found pretty much almost every Ambon Island waters but has not been used optimally. This study aims to determine the physical-chemical characteristics of some waters Diadema setosum Ambon Island. The study was conducted in June 2016 in the village of Poka Martafons coastal waters, beaches and beach Sopapei Suli Waai Waai village. The method used in this research is survey method, observation and sampling methods. The parameters observed in this study is the physical parameters of water chemistry, yield, morphometric, moisture, protein, fat, ash, carbohydrates from setosum Diadema urchins gonads. The data obtained are presented in the form of figures and tables. The results showed the diameter of the shell and the body weight of the Diadema setosum urchins coastal waters Martafons ranged from 36.5 to 61.7 mm and 23.6 -100.8 g; Sopapei coast from 34.8 to 79.8 mm and 23.8 to 107 grams; Waai coast ranged from 33 to 64.5 mm and 13.9 to 91.1 g. The average weight of the Diadema setosum urchins from Ambon Island waters ranges from 30-50 grams with a diameter of 40-50 mm shell. The growth pattern of the urchins Diadema setosum third alometrik waters are negative. The percentage yield of gonadal smaller than the shell and innards. Gonadal yield of 1.5 to 5%, while the shell reaches more than 85%. The average color of the gonads diadema setosum of coastal waters Martafons, sopapei and Waai is yellow to pale yellow compact textured, gonad weight below 10%. The water content of the gonads (73.76 to 84.13)%, ash (0.20 to 2.12)%, fat (3.47 to 5.81)%, protein (5.40 to 17.69)%, carbohydrates (2.11 to 7.50)%. In general, the physical-chemical characteristics of the sea urchin better Sopapei coastal waters of the coast and beaches Martafons Waai. ABSTRAK Keberadaan Diadema setosum cukup banyak hampir dijumpai disetiap perairan Pulau Ambon namun belum dimanfaatkan secara optimal. Penelitian ini bertujuan untuk menentukan karakteristik fisik-kimia Diadema setosum dari beberapa perairan Pulau Ambon. Penelitian dilakukan pada bulan Juni 2016 di perairan pantai Martafons Desa Poka, pantai Sopapei Desa Suli dan pantai Waai Desa Waai. Metode yang digunakan dalam penelitian ini adalah metode survey, observasi dan metode sampling. Parameter yang diamati dalam penelitian ini yaitu parameter fisik kimia perairan, rendemen, morfometrik, kadar air, protein, lemak, abu, karbohidrat dari gonad bulu babi Diadema setosum. Data yang diperoleh disajikan dalam bentuk gambar dan tabel. Hasil penelitian menunjukkan diameter cangkang dan bobot tubuh bulu babi Diadema setosum dari perairan pantai Martafons berkisar antara 36,5-61,7 mm dan 23,6 -100,8 gr; pantai Sopapei 34,8-79,8 mm dan 23,8-107 gr; pantai Waai berkisar antara 33-64,5 mm dan 13,9-91,1 gr. Rata-rata bobot tubuh bulu babi Diadema setosum dari perairan Pulau Ambon berkisar 30-50 gr dengan diameter cangkang 40-50 mm. Pola pertumbuhan bulu babi Diadema setosum dari ketiga perairan bersifat alometrik negatif. Persentase rendemen gonad lebih kecil dari cangkang dan jeroan. Rendemen gonad 1,5-5%, sedangkan cangkang mencapai lebih dari 85%. Rata-rata warna gonad Diadema setosum dari perairan pantai Martafons, Sopapei dan Waai berwarna kuning sampai kuning pucat bertekstur kompak, berat gonad dibawah 10%. Kadar air gonad (73,76-84,13)%, abu (0,20-2,12)%, lemak (3,47-5,81)%, protein (5,40-17,69)%, karbohidrat (2,11-7,50)%. Secara umum karakteristik fisik-kimia bulu babi dari perairan pantai Sopapei lebih baik dari pantai Martafons dan pantai Waai. Kata kunci: Diadema setosum, komposisi kimia, karakteristik fisik, Pulau Ambon